Cognitive function in early and later life is associated with blood glucose in older individuals: analysis of the Lothian Birth Cohort of 1936 - Altschul, Drew M. (Diabetologia, 2018)
AIMS/HYPOTHESIS: The aim of this study was to examine whether cognitive function in early and later life, and decline in cognitive function from age 70 to 79 years, are associated with high blood glucose, as measured by HbA(1c), at baseline (age 70), and changes in blood glucose from age 70 to 79. METHODS: Participants (n = 1091) in the Lothian Birth Cohort of 1936 were examined. Fourteen tests were used to assess cognitive functions, grouped into four domains: visuospatial ability, processing speed, memory and crystallised ability. Test results, and measurements of HbA(1c) and other health variables, were collected at each of four waves of assessment: at the mean age of 70, 73, 76 and 79 years. Data on cognitive function at age 11 was also available for this cohort. Latent growth curve modelling was performed and statistical controls for known risk factors were introduced. RESULTS: Higher age 11 cognitive function predicted lower HbA(1c) level at age 70 (p < 0.001). Higher cognitive function at age 70 was related to a comparatively smaller increase in HbA(1c) levels from age 70 to 79 (p < 0.001). HbA(1c) from age 70 to 79 did not have any consistent association with change in cognitive function from age 70 to 79. These associations survived adjustments for age, sex, education, APOE*ε4, smoking history, cardiovascular disease history, hypertension history, BMI and corrections for multiple testing. CONCLUSIONS/INTERPRETATION: Our results show that, among older individuals, high blood glucose is consistently predicted by lower cognitive function. Clinical care that examines and tracks cognitive function, while also taking the positive effects of maintaining cognitive function and emulating healthy behaviours associated with higher cognitive function into account, may be one approach for protecting at-risk individuals from elevated blood glucose and subsequent type 2 diabetes mellitus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-018-4645-8) contains peer-reviewed but unedited supplementary material, which is available to authorised users.